The role of the internal audit function in assessing the risks of economic and social factors using the risk matrix : Applied research in the General Land Transport Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:At present, the external risk environment is now competing with the internal risk environment as a primary focus for risk management, due to the dominance of the sustainability agenda, as these issues pose real challenges to the company, because internal audit contributes to adding value through evaluating and improving risk management processes, as the research aims to shed light The role of internal audit in developing a plan to evaluate the factors of the external environment represented by (economic and social) factors to determine the work centers according to the degree of their exposure to risks in order to control them and reduce them to the level acceptable to management. Its importance stems from the scarcity of studies and research that have addressed these factors and evaluated their impact on the company’s operations mediated by the function. Internal audit to identify the risks associated with it. Therefore, those concerned with internal audit and management should collect as much information as possible about the company’s external environment to design a control system that is compatible with the surrounding risks and not waste time in relatively unimportant areas. The researcher uses the risk matrix to link work centers and risks and communicate the research reached a set of conclusions, perhaps the most important of which is that Iraqi public companies are surrounded by many risks that must be dealt with to avoid future risks, perhaps the most prominent of which are the economic conditions as well as a weakness in commitment to social responsibility. The research concluded with several recommendations, the most important of which is the need for the competent authorities in the auditing profession to hold seminars and workshops. For internal auditors to identify and evaluate the risks of economic and social factors to determine the degree of their impact on their departments, while developing a guide and indicators for how they deal with these risks and taking them into account when developing the audit plan to design audit procedures to avoid these risks.